The targeting of tumor-associated macrophages by vaccination - Mads Hald Andersen (Cell Stress, 2019)
Many different therapeutic strategies focus on targeting tumor-associated macrophages (TAMs), due to their vital role in creating an immune suppressive tumor microenvironment (TME) with the aim to deplete, reprogram or target the functional mediators secreted by these cells. Immune modulatory vaccination is an emerging strategy to target immune suppressive myeloid populations in the TME. In contrast to the other clinical strategies that target TAMs, this combines both TAM depletion (through direct killing by cytotoxic T cells) and TAM reprogramming (by introducing pro-inflammatory cytokines into the immune suppressive microenvironment).